σ factor selectivity of Escherichia coli RNA polymerase: role for CRP, IHF and Lrp transcription factors - Colland, Frédéric (Oxford University Press, 2000)
osmY is a stationary phase-induced and osmotically regulated gene in Escherichia coli that requires the stationary phase RNA polymerase (Eσ(S)) for in vivo expression. We show here that the major RNA polymerase, Eσ(70), also transcribes osmY in vitro and, depending on genetic background, even in vivo. The cAMP receptor protein (CRP) bound to cAMP, the leucine-responsive regulatory protein (Lrp) and the integration host factor (IHF) inhibit transcription initiation at the osmY promoter. The binding site for CRP is centred at –12.5 from the transcription start site, whereas Lrp covers the whole promoter region. The site for IHF maps in the –90 region. By mobility shift assay, permanganate reactivity and in vitro transcription experiments, we show that repression is much stronger with Eσ(70) than with Eσ(S) holoenzyme. We conclude that CRP, Lrp and IHF inhibit open complex formation more efficiently with Eσ(70) than with Eσ(S). This different ability of the two holoenzymes to interact productively with promoters once assembled in complex nucleoprotein structures may be a crucial factor in generating σ(S) selectivity in vivo.